Relevansi Keberadaan Pidana Penjara dalam Perspektif Hukum Islam dan Hukum Adat - Khasanah, Maui Dhotul; Amelia, Marisa; Mutiarani, Diani; Alkaff, Fitriyah; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Imprisonment is a normal form of sanction applied in the modern legal system. However, its existence is often debated from the perspective of Islamic law and customary law, which have different approaches to upholding justice in redressing violations. This research aims to analyze the concept of imprisonment in Islamic law and customary law, including its normative, philosophical basis and application in society. In Islamic law, the main emphasis is on restorative justice through hudud, qisas, and ta'zir, while customary law places more emphasis on resolutions based on deliberation, peace, and restoration of social relations. This research uses qualitative methods with a normative and sociological approach, and combines analysis of Islamic doctrine, customary nuoma, and legal practices in Indonesia. The results of this research show that imprisonment is not actually regulated in Islamic law or traditional customary law, but its existence can be adjusted as a form of ta'zir or dynamic adaptation of customary law. However, the application of imprisonment must still consider the values ​​of justice, humanity and local wisdom. It is hoped that this research can contribute to the development of criminal law that is harmonious with Islamic values ​​and customs in Indonesia.